Stock Market Vulnerability to the COVID-19 Pandemic: Evidence from Emerging Asian Stock Market - RABHI, Ayoub (Journal of Advanced Studies in Finance; Vol 11 No 2 (2020): JASF Volume XI Issue 2(22) Winter 2020DO - 10.14505//jasf.v11.2(22).06, 2020)
This paper studies empirically the emerging Asian stock market vulnerability to pandemics. Taking the Covid-19 virus as a case study, we used the ARDL panel data approach to investigate the impact of the daily Covid-19 confirmed cases along with a behavioral component based on a triggering fear event related to news about Covid-19 deaths. The results indicate that both the reported daily growth of Covid-19 confirmed cases along with the triggering fear event related to news about death, affected the Asian stock markets performance negatively, other variables such as oil price, gold price, exchange rates, and the US stock market were also found to be determinants of the Asian stock markets during the studied period.